Acupuncture as an intervention to reduce alcohol dependency: a systematic review and meta-analysis. Issue 1 (December 2016) - Southern, Charlotte; Lloyd, Charlie; Liu, Jianping; Wang, Congcong; Zhang, Tingting; Bland, Martin; MacPherson, Hugh
Abstract Background Acupuncture has been widely used as a treatment for alcohol dependence. An updated and rigorously conducted systematic review is needed to establish the extent and quality of the evidence on the effectiveness of acupuncture as an intervention for reducing alcohol dependence. This review aimed to ascertain the effectiveness of acupuncture for reducing alcohol dependence as assessed by changes in either craving or withdrawal symptoms. Methods In this systematic review, a search strategy was designed to identify randomised controlled trials (RCTs) published in either the English or Chinese literature, with a priori eligibility criteria. The following English language databases were searched from inception until June 2015: AMED, Cochrane Library, EMBASE, MEDLINE, PsycINFO, and PubMed; and the following Chinese language databases were similarly searched: CNKI, Sino-med, VIP, and WanFang. Methodological quality of identified RCTs was assessed using the Jadad Scale and the Cochrane Risk of Bias tool. Results Fifteen RCTs were included in this review, comprising 1378 participants. The majority of the RCTs were rated as having poor methodological rigour. A statistically significant effect was found in the two primary analyses: acupuncture reduced alcohol craving compared with all controls (SMD = −1.24, 95% CI = −1.96 to −0.51); and acupuncture reduced alcohol withdrawal symptoms compared with all controls (SMD = −0.50, 95% CI = −0.83 to −0.17). In secondary analyses: acupuncture reduced craving compared with sham acupuncture (SMD = −1.00, 95% CI = −1.79 to −0.21); acupuncture reduced craving compared with controls in RCTs conducted in Western countries (SMD = −1.15, 95% CI = −2.12 to −0.18); and acupuncture reduced craving compared with controls in RCTs with only male participants (SMD = −1.68, 95% CI = −2.62 to −0.75). Conclusion This study showed that acupuncture was potentially effective in reducing alcohol craving and withdrawal symptoms and could be considered as an additional treatment choice and/or referral option within national healthcare systems.